2017
DOI: 10.15171/jcs.2017.029
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative Study on women’s experiences of Intrapartum Care at Tamale Teaching Hospital, Ghana.

Abstract: Introduction: Labor and delivery process is an exciting, anxiety-provoking, but rewarding time for a woman and her family after successful delivery of a newborn. The intrapartum period is the time where mothers expect more care. Taking care of a mother through delivery with no side effects is the task of a professional midwife who is trained with the skill to take the responsibility of caring for mothers and babies. Therefore, the aim of this study was to explore mother’s experiences regarding quality of intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…They highlighted the importance of midwives showing interest in their wellbeing, and providing clear explanations to procedures. This is in line with prior studies where women reported being satisfied with the information they received from midwives [7, 47] and recommended that effective communication and relational skills of healthcare personnel are major determinants of trust between care providers and women [7, 47]. Midwives need to be more proactive in the provision of information and explanations to procedures to ensure effective and cooperative maternity care, as some participants, particularly those who underwent emergency CS were distraught with the inadequate provision of information about the surgical procedure.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…They highlighted the importance of midwives showing interest in their wellbeing, and providing clear explanations to procedures. This is in line with prior studies where women reported being satisfied with the information they received from midwives [7, 47] and recommended that effective communication and relational skills of healthcare personnel are major determinants of trust between care providers and women [7, 47]. Midwives need to be more proactive in the provision of information and explanations to procedures to ensure effective and cooperative maternity care, as some participants, particularly those who underwent emergency CS were distraught with the inadequate provision of information about the surgical procedure.…”
Section: Discussionsupporting
confidence: 91%
“…Childbirth remains a uniquely multifaceted, mentally-cognitive and a major life experience to women [7, 8]. It is composed of a variety of psychosocial and emotional aspects and creates memories, sometimes bad experiences and unmet expectations which may leave the mother with memories for life [8].…”
Section: Introductionmentioning
confidence: 99%
“…Migrants,around the world, generally have negative experiences with maternalcare in their new countries. Previous studies have reported that migrant women in developing countries usuallydo not receive timely, appropriate or high-quality maternal health care [15][16][17]. A systematic and comparative review of immigrant and non-immigrant women'sexperiences of maternity care, identi ed that immigrant women were less positive about the care they received than non-immigrant womenbecause of reasons such ascommunication problems and lack of familiarity with care systems [18].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the important role midwives play in maternal health care in rural settings, few or no study has been carried out or documented about the perspectives of midwives working in rural and deprived areas of northern Ghana with regards to the challenges they experience in providing midwifery care, or what support and systems are needed to ensure that rural childbearing women and their newborns are provided with the highest attainable standard of digni ed and respectful midwifery care. Most of the previous research studies carried out in the study setting were focused on the experiences of mothers utilising skilled birth care [12,13,14,15]. This study was aimed at exploring and describing the challenges experienced by midwives providing midwifery care in rural northern Ghana.…”
Section: Introductionmentioning
confidence: 99%